Multifaceted bioinspired hyperbranched polyurethane nanocomposite as a non-contact triggered self-healing material - R. Duarah; A. Deka; N. Karak (eXPRESS Polymer Letters, 2020)
The current investigation reports in situ fabrication of hyperbranched polyurethane (HPU) nanocomposites with different weight percentages of functionalized silica nanoparticle as nano-reinforcing material. Silica nanoparticles were functionalized with sodium dodecyl sulfate and polyethylene glycol using a facile, simple one-pot method. The nanomaterial and the HPU nanocomposites were assessed by Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet (UV)-visible, X-ray Diffraction (XRD), Transmission Electron Microscope (TEM), mechanical and thermal studies. The fabricated nanocomposites demonstrated notable tensile strength (25.8 MPa), excellent elongation at break (1495%), outstanding toughness (340.88 MJ・m–3), good scratch hardness (7.5 kg), significant impact strength (19.02 kJ・m–1) and sufficient improvement in hydrophobicity (105.2° from 76.7°). They also demonstrated remarkable non-contact triggered thermo-responsive shaperecovery (97.6–-99.4%). Moreover they displayed efficient self-healing behavior within just 20 s under microwave (360 W). The nanocomposites also exhibited biodegradation by bacterial strains, Pseudomonas aeruginosa, and Bacillus subtilis. Thus, the present work promotes this biodegradable nanocomposite as a potential high performing self-healing and selfcleaning material.